Guidelines for Sustainability Assessment in Food and Agriculture - El Hage, Nadia (Food and Agriculture Organisation of the United Nations, 2012)
The ecological, economic and social principles of sustainable development (WCED, 1987) received nearly universal agreement during and following the 1992 Earth Summit. One of the summit‘s major outcomes, Agenda 21, includes a whole chapter (Chapter 14) on sustainable agriculture and rural development. Much progress has been made in the past two decades. For most social and economic Millennium Development Goals, improvements have been substantial (UN, 2011). Global per capita Gross National Income has more than doubled between 1992 and 2010 (from 5,035 current interna-tional USD at PPP to 11,058; World Bank, 2011). Yet, reaching the poorest, all over the world, re-mains a challenge (UN, 2011) and it is today generally recognised that GDP growth alone is not a sufficient indicator of development progress. The number of undernourished people was estimated by FAO to be 925 million in 2010. This figure has increased by 75 million people since 1990-92 (FAO, 2010a). Rockström et al. (2009) estimate that humanity has transgressed three of the environmental planetary boundaries within which we can operate safely, namely for climate change, biodiversity loss and changes to the global nitrogen cycle. Boundaries for ocean acidification and possibly the global phosphorus cycle might also be close to being crossed.global phosphorus cycle might also be close to being crossed. As agricultural land and forests occupy more than 60% of terrestrial surface, and fishery activities can be found on virtually any water body, agriculture, forestry and fisheries are major contributors to the ecological footprint of humanity. For example, 31% of global greenhouse gas emissions have been attributed to agriculture and forestry (IPCC, 2007). Agriculture alone accounts for 70% of global freshwater withdrawals (FAO, 2011). On the other hand, farming, animal husbandry, forestry and fisheries produce the food and renewable materials basis of humanity’s existence and provide liveli-hoods to more than 2.6 billion people (FAOSTAT, 2011), including ...